On the evaluation of thermo-acoustic and non-linear properties of polymers and liquids - SHARMA, B. K. (Archives of Acoustics, 1986)
Thermo-acoustic properties of polymers are calculated in terms of the temperature and pressure derivatives of the bulk modulus on the basis of an assumption that the isochoric temperature coefficient of the bulk modulus is an important factor. An attempt has made to obtain correlations between the thermoacoustic, anharmonic and nonlinear properties with the molecular force constants governing the intermolecular potential. These properties have been expressed in terms of the volume expansion which is found as the controlling factor for their dependence on temperature and volume for liquids.